With tax perspective, the relations between European Union and Turkey and customs union - Er, Yunus Özay (My University, 2005)
This study deals with the relations between Turkey and the European Union in the respect of the Customs Union with tax perspective. After a brief introduction part, the Thesis is divided into two main parts. In first part, the process passed from the foundation phases of the European Union and Turkey's position in these periods, the Customs Union application of the European Union and Turkey's part in that relevant Customs Union formation are examined in turns and with a historical perspective. In second part, again within the concept of the Customs Union, the tax policies of the European Union are initially expressed. Afterwards, in same part of the thesis, The Turkish Tax System is put forward with its main points and these two tax system is examined with a comparative perspective. After a conclusion part, where the statistical information mentioned, my thesis is finished with a general conclusion part where I express my own ideas about the relevant subject. Due to its special type, the relevant relations between Turkey and the European Union initially examined with historical perspective. By giving some examples from the decisions of the European Court of Justice and with some figures and numbers, the content of the thesis is tried to be supported The result of this study shows us that the Customs Union application of Turkey and the Turkish Tax System take the European Union and her applications as a model and so there are not so big differences between the two sides' policies. Furthermore, the differences in question are not the dissolvable impediments to reach the full membership and can be solved in a certain time period. iv.

Bu çalışma Türkiye-Avrupa Birliği ilişkilerini vergi boyutu ile Gümrük Birliği çerçevesinde ele almaktadır. Tez temelde kısa bir giriş kısmının ardından 2 ana bölüme ayrılmaktadır. Birinci bölümde, Avrupa Birliğinin kuruluşundan bugüne kadar geçen süreç ve Türkiye'nin ilgili süreçteki yeri, Avrupa Birliği Gümrük Birliği uygulaması ve Türkiye'nin Gümrük Birliği yapılanması içerindeki yeri sırası ile ve tarihi bir bakış açısı ile incelenmektedir. İkinci bölümde is yine Gümrük Birliği çerçevesinde Avrupa Birliğinin vergi politikaları öncelikli olarak ele alınmaktadır. Ardından yine aynı bölümde Türk vergi sistemi ana hatları ile ortaya konmakta olup, her iki vergi sistemi karşılaştırmalı bir bakış açısı çerçevesinde irdelenmiştir. Tezim rakamsal verilerin ortaya konduğu sonuç bölümünden sonra kişisel görüşlerimi belirtmiş olduğum genel bir sonuç bölümü ile sona ermektedir. Kendine has özellikleri nedeni ile Türkiye-Avrupa Birliği ilişkileri öncelikli olarak tarihi çerçevede ele alınmıştır. Adalet Divanı kararları ve belli başlı rakamsal veriler ve tablolar vasıtası ile de tezin içeriği desteklenmeye çalışılmıştır. Sonuç bize göstermektedir ki, Türkiye'nin Gümrük Birliği uygulaması ve Türk Vergi Sistemi kendisine Avrupa Birliği'ni model almaktadır ve bu nedenle de iki tarafın aralarında bu bağlamda üyeliği engelleyici bazda farklar bulunmadığı, mevcut farkların da belirli bir zaman içerisinde çözülebileceği düşünülmektedir.
Keywords: Avrupa Birliği_Hukuk